Assessment of Tooth Wear Among Glass Factory Workers: WHO 2013 Oral Health Survey - Chaturvedi, Pulkit (J Clin Diagn Res, 2015)
BACKGROUND: Glass factory workers are often exposed to the hazardous environment that leads to deleterious oral health and subsequently, general health. We planned to determine the effects of the particulates present in the milieu on the tooth wear among workers. AIM: To assess tooth wear among glass factory workers in Jaipur, Rajasthan, India. SETTINGS AND DESIGN: A descriptive cross-sectional survey was conducted among 936 glass workers in Jaipur, Rajasthan, India from January-June 2014. MATERIALS AND METHODS: A survey proforma was designed for tooth wear evaluation with the help of WHO Oral Health Assessment form 2013 (for adults). Information regarding oral health practices, adverse habits and dietary habits, demographic details was gathered and clinical parameters were recorded. STATISTICAL ANALYSIS: The Chi–square test, t–test, One-way Analysis of Variance and a Stepwise multiple linear regression analysis. RESULTS: The most prevalent form of erosion was enamel erosion (589, 62.93%) with few subjects of deeper dentinal erosion and the difference was statistically significant (p=0.001). Dental erosion was found to be higher among males compared to females. Years of experience and educational status were identified as best predictors for dental erosion. CONCLUSION: It was concluded that there was considerable evidence of dental erosion found among the factory workers. Due to ignorance on social, cultural and health aspects, professional approach with regular dental care services for detection of early symptoms and planning of preventive strategies is warranted.